CT and MR Imaging Findings in Methanol Intoxication - Blanco, M.; Casado, R.; Vázquez, F.; Pumar, J.M. (American Journal of Neuroradiology, 2006)
SUMMARY: We present the CT and MR imaging findings in acute methanol intoxication in a 35-year-old man who was admitted to the emergency department with weakness, blurred vision, mild bilateral areactive mydriasis, and a progressive decrease in the level of consciousness. CT and MR imaging showed bilateral putaminal hemorrhagic necrosis and subcortical white matter lesions with peripheral contrast enhancement. There was only partial improvement in patient’s Glasgow Coma Scale score during follow-up.